-b-(13=4b)=-3(5-9b)+2

Simple and best practice solution for -b-(13=4b)=-3(5-9b)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -b-(13=4b)=-3(5-9b)+2 equation:



-b-(13=4b)=-3(5-9b)+2
We move all terms to the left:
-b-(13-(4b))=0
We add all the numbers together, and all the variables
-b-(-4b+13)=0
We add all the numbers together, and all the variables
-1b-(-4b+13)=0
We get rid of parentheses
-1b+4b-13=0
We add all the numbers together, and all the variables
3b-13=0
We move all terms containing b to the left, all other terms to the right
3b=13
b=13/3
b=4+1/3

See similar equations:

| x+2.9=6.3 | | 6+x=-7+2x | | 28+7x=49+7x | | -17(y+3)+6(4y-3)=6(y-3)+14 | | 1x=11.75 | | 83=5(7-a)-a | | 3x+3-6=-9 | | x/2+17=17 | | 2x-2=-2x=12 | | 5f+9=12f-26 | | -3z-9=-42 | | -4x+6/7=2 | | 3x2-26x+32=0 | | 18x+x=205 | | 4(x+2)+8x=16 | | 17x+8=11x+6 | | -1/2x-5/3=-7/12 | | -7(5+3x)=-30-7x | | 30m+500=7,700 | | 60+5x2=140 | | -3+2k=k-1 | | -4-12=8x+24 | | 3x+900=2x+1000 | | 3/4=3/8x-2 | | -95=x-7(8+2x) | | 11÷7=2x | | -6y=2y+4=14 | | 3x+3=1x+(-5) | | 4(5x-7)=10x2 | | 5(2x+10)+30=6x+104 | | 5+4x-7=4x-22x | | -3(14+5r)2r=-14(r+3) |

Equations solver categories